Redesigning the Balanced Scorecard through Agentic AI: Implications for organizational governance and social change - Naomi Miryam (PT Bina Perfidia Akademia, 2026)
The rapid advancement of Artificial Intelligence (AI) has transformed organizational performance management systems; however, previous studies have primarily viewed AI as an analytical tool and have not integrated Agentic AI into the Balanced Scorecard framework to support adaptive organizational governance. This study aims to develop a conceptual model of the Redesigned Balanced Scorecard through Agentic AI and examine its implications for organizational governance and social change. The study employed a library research approach with conceptual analysis by synthesizing the literature on the Balanced Scorecard, Agentic AI, performance management, and organizational governance. The findings indicate that integrating Agentic AI transforms the Balanced Scorecard through continuous monitoring, adaptive decision-making, and Adaptive KPI, resulting in six conceptual implications: adaptive performance management, continuous monitoring, data-driven decision-making, dynamic performance indicators, more transparent governance, and more objective performance assessment. This study contributes by proposing a novel conceptual framework that extends the role of the Balanced Scorecard as an adaptive performance management system in the era of machine autonomy. Abstrak Perkembangan Artificial Intelligence (AI) telah mendorong transformasi sistem manajemen kinerja organisasi. Namun, penelitian sebelumnya masih memosisikan AI sebagai alat analitik dan belum mengintegrasikan kemampuan Agentic AI ke dalam kerangka Balanced Scorecard untuk mendukung tata kelola organisasi yang adaptif. Penelitian ini bertujuan mengembangkan model konseptual Redesigned Balanced Scorecard through Agentic AI serta menganalisis implikasinya terhadap organizational governance dan social change. Penelitian ini menggunakan pendekatan library research dengan analisis konseptual melalui sintesis literatur mengenai Balanced Scorecard, Agentic AI, manajemen kinerja, dan tata kelola organisasi. Hasil penelitian menunjukkan bahwa integrasi Agentic AI mentransformasi Balanced Scorecard melalui penerapan continuous monitoring, adaptive decision-making, dan Adaptive KPI, sehingga menghasilkan enam implikasi konseptual berupa manajemen kinerja adaptif, pemantauan berkelanjutan, pengambilan keputusan berbasis data, indikator kinerja dinamis, tata kelola yang lebih transparan, serta penilaian kinerja yang lebih objektif. Penelitian ini berkontribusi dengan menawarkan model konseptual baru yang memperluas peran Balanced Scorecard sebagai sistem manajemen kinerja adaptif pada era machine autonomy.